COGNITIVE ASPECT OF WORD FORMATION (Scientific journal of the Fergana State University, 2023)
This article deals with the issues of the cognitive aspect of word formation. The purpose of this research is to identify the cognitive foundations of non-derivative, derivative, compound words. In the research of is used the methods of conceptual analysis and cognitive modeling. Words formed on the basis of cognitive models are interpreted as a verbalization of human knowledge. Also,secondary interpretation is seen as a cognitive activity that is based on the linguistic creativity and involves selectivity in the processing of knowledge.